PENGARUH KECERDASAN SPIRITUAL TERHADAP PERILAKU PROSOSIAL SISWA DI SMA NEGERI 1 MUARO JAMBI - Istiqomah, San Putri; Harahap, Nur Hasanah; Gutji, Nelyahardi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research was motivated by the results of preliminary data found by researchers which showed that there were still many students who had low prosocial behavior. Students lack initiative to help others. If this is not addressed, it can lead to an increasingly indifferent attitude towards other people, which can later result in them growing into people who have highly individual characteristics and do not like to help selflessly. The aim of this research is to determine the influence of spiritual intelligence on the prosocial behavior of students at SMA N 1 Muaro Jambi. With a research population of 262 students in grades VII and VIII. The type of research used by researchers is qualitative research using an ex post facto research approach. The analysis used to determine the influence of each variable uses a simple linear regression analysis technique. Subjects in this study were selected using a simple random sampling technique, data collection tools using a questionnaire. The results of the research show that there is a positive influence between spiritual intelligence on students' prosocial behavior at SMA Negeri 1 Muaro Jambi. With a correlation value of 0.508 and a regression of 0.258, which means that the influence of the independent variable (spiritual intelligence) on the dependent variable (prosocial behavior) is 25.8%. Thus, by using regression interpretation criteria, the R square value (0.258) is in the range of 0.17-0.49, which means that spiritual intelligence has a fairly strong influence on prosocial behavior.